2022
DOI: 10.1016/j.acap.2021.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Adolescent Discrepancies in Adolescent Recreational Screen Time Reporting During the Coronavirus Disease 2019 Pandemic

Abstract: Objective To describe the relationship between parent and adolescent reports of adolescent recreational screen time and to determine sociodemographic predictors of recreational screen time reporting differences during the COVID-19 pandemic. Methods We analyzed data from the Adolescent Brain Cognitive Development Study (ABCD, N=5,335, ages 10-14) a national prospective cohort study in the US collected in May 2020. We compared parent-reported, adolescent-reported, and a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“… 42 Parents underestimate adolescents’ social media use. 43 Heavy parent screen use has been shown to predict child screen use and can lead to distracted parenting, also known as “technoference” or “technology interference.” 44 Technology interference may be influenced by parental education status, household income, and race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“… 42 Parents underestimate adolescents’ social media use. 43 Heavy parent screen use has been shown to predict child screen use and can lead to distracted parenting, also known as “technoference” or “technology interference.” 44 Technology interference may be influenced by parental education status, household income, and race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…With the unknown lasting impacts of COVID-19 and associated lockdowns on children’s screen time, there has been a call for more qualitative research with families [ 21 ] to inform the redesign or development of new intervention strategies to minimise excessive screen use in the progression to ‘COVID-19 normal’. It is crucial to gain insights from both parents and children due to discordance in their reporting of screen time engagement during COVID-19 [ 22 ] and the differing impact screen time may have on familial interactions [ 14 ]. Further, ensuring end-user voice is included in the development of intervention programs can enhance the use, and effectiveness, of the program [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electronic media use was obtained from parent report which can have discrepancies with the child or adolescent's report of their media and may be influenced by recall and social desirability bias. However, previous studies have found these discrepancies in duration to be fairly small with some studies reporting within 10 to 30 minutes difference between parent and adolescent responses (Nagata et al, 2021;Wood et al, 2019). This study also focused solely on ADHD and did not examine other possible co-occurring mental or emotional health conditions.…”
Section: Discussionmentioning
confidence: 95%